(2R)-2-(1,3-Dioxoisoindolin-2-yl)-4-(methylsulfanyl)butanoic acid - Raza, Abdul Rauf (International Union of Crystallography, 2009)
The title compound, C(13)H(13)NO(4)S, the 1,3-dioxoisoindolin-2-yl unit is planar (r.m.s. deviation 0.0192 Å) and is oriented at a dihedral angle of 79.14 (18)° to the carboxylate group. An intramolecular C—H⋯O hydrogen bond leads to the formation of a planar (r.m.s. deviation 0.0419 Å)R(5) ring motif. In the crystal, molecules are connected through O—H⋯O and C—H⋯O hydrogen bonds with R (2) (2)(9) ring motifs into chains extending along the b axis.